Residual brewer’s Saccharomyces cerevisiae yeasts as biofertilizers in horticultural seedlings: towards a sustainable industry and agriculture - Vargas, Mercedes Fabiana; Mestre, María Victoria; Vergara, Cristina; Maturano, Paola; Petrignani, Diego; Pesce, Virginia; Vazquez, Fabio (Frontiers in Industrial Microbiology, 2024)
The food industry generates substantial amounts of organic waste often underutilized within the system. Craft beer production, experiencing global rapid expansion, contributes to this waste stream with byproducts such as spent grain, trub, and yeast. Many craft beer industries discharge yeast residue directly into public water bodies. In recent years, yeasts have garnered attention for their potential to enhance plant growth and contribute to sustainable agriculture. This study focuses on characterizing Saccharomyces cerevisiae yeast collected at the end of the craft beer fermentation process. Biomass characterization was conducted, and the yeast’s effect on lettuce and tomato seeds and seedlings was evaluated at four concentrations (105, 106, 107, and 108 cells mL−1) in sterile substrate. After 28 days, plant height, leaf number, fresh and dry weights of both aboveground and root parts, as well as chlorophyll content, were analyzed. The most effective concentration (107 cells mL−1) was applied to tomato seedlings in sterile substrate, compared with a commercial organic fertilizer. After 21 days, growth parameters were assessed. The study demonstrated that increasing yeast doses up to 108 cells mL−1 positively affects seed germination and seedling development. Notably, a dose of 107 cells mL−1 proved effective for application in seedlings as an organic amendment and substitute for commercial products. This integrated approach showcases the potential of yeasts in sustainable agriculture, utilizing byproducts from the food industry to enhance crop performance and mitigate environmental pollution.